89 Chronic disseminated candidiasis treated with adjuvant corticosteroid treatment. (30th November 2020) - Rogosic, Srdan; Patterson, Charlotte; Bartram, Jack; Pavasovic-Jovanovic, Vesna; Samarasinghe, Sujith; Ancliff, Philip; Rao, Anupama; O'Connor, David; Vora, Ajay; Ghorashian, Sara
Abstract : Background: Chronic disseminated candidiasis (CDC) can be a severe infection in immunocompromised patients. CDC/IRIS is an associated immune reconstitution syndrome most commonly characterised by prolonged fever despite adequate antimicrobial cover, raised inflammatory markers and typical radiological changes, often occurring during neutrophil recovery and causing significant morbidity in itself. Objective: To establish the outcomes of corticosteroid use in CDC/IRIS patients. Methods: In this retrospective study, we included all the patients with CDC/IRIS treated with corticosteroids in our Department from March 2017 until May 2020. We defined CDC/IRIS with persistent fevers, resistant to a minimum of 2 weeks of antifungal treatment, raised inflammatory markers and accompanying radiological changes. The data was collected through searches in the laboratory system and the medical notes. Results: 6 patients fit the criteria for CDC/IRIS. All the patients received a substantial course of antifungals before starting corticosteroids (median 47.5 days (range 15–107)). All patients had raised CRP (median 186 (range 77–271)). 5 patients had positive radiological changes in the spleen, liver or kidney. 1 patient only had pulmonary changes. The duration of fevers prior to starting corticosteroids was 46 days (range 21–96). Most patients (5/6) received a short course of methylprednisolone, dexamethasone or hydrocortisone, followed by prednisolone for the rest of the treatment. The median duration of corticosteroid treatment was 94 days (range 34–400). Fever resolved on the same day or the day after starting corticosteroids in 5/6 patient. 5/6 patients remained apyrexial more than seven days after stopping corticosteroids. Conclusion: These findings confirm that adjuvant corticosteroids are helpful in the management of CDC/IRIS. However, prolonged corticosteroid treatment has associated complications and can impair anti-fungal immune responses so its use has to be judged carefully. In this series, all patients derived clinical benefit and there were no cases of clinical deterioration related to progression of fungal infection.